Authority and identity in emerging Christianities in Asia Minor and Greece - Breytenbach, Cilliers, 1954-; Ogereau, Julien M., 1981- (Ancient Judaism and Early Christianity, 2018)
This book explores how early Christian communities constructed, developed, and asserted their identity and authority in various socio-cultural contexts in Asia Minor and Greece in the first five centuries CE. With the help of the database Inscriptiones Christianae Graecae ( ICG ), special attention is given to ancient inscriptions which represent a rich and valuable source of information on the early Christians' social and religious identity, family networks, authority structures, and place and function in society. This collection of essays by various specialists of Early Christianity, Epigraphy, and Late Antiquity, offers a broad geographical survey of the expansion and socio-cultural development of Christianity/ies in Asia Minor and Greece, and sheds new light on the religious transformation of the Later Roman Empire.